2007
DOI: 10.1097/01.anes.0000287009.46896.a7
|View full text |Cite
|
Sign up to set email alerts
|

A Single Dose of Propofol at the End of Surgery for the Prevention of Emergence Agitation in Children Undergoing Strabismus Surgery during Sevoflurane Anesthesia

Abstract: In children undergoing strabismus surgery, 1 mg/kg propofol at the end of surgery after discontinuation of sevoflurane decreases the incidence of agitation and improves parents' satisfaction without delaying discharge from the postanesthesia care unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
168
4
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(187 citation statements)
references
References 28 publications
13
168
4
1
Order By: Relevance
“…Various strategies have been attempted to reduce the incidence of emergence agitation associated with sevoflurane anaesthesia in children, including the use of non-steroidal anti-inflammatory drugs, 6 propofol, 10 and switching inhaled anaesthetics after induction. 21 No strategy has gained widespread acceptance, and preventing or managing emergence agitation with analgesics and sedatives can delay recovery and discharge from the PACU.…”
Section: Discussionmentioning
confidence: 99%
“…Various strategies have been attempted to reduce the incidence of emergence agitation associated with sevoflurane anaesthesia in children, including the use of non-steroidal anti-inflammatory drugs, 6 propofol, 10 and switching inhaled anaesthetics after induction. 21 No strategy has gained widespread acceptance, and preventing or managing emergence agitation with analgesics and sedatives can delay recovery and discharge from the PACU.…”
Section: Discussionmentioning
confidence: 99%
“…4 Propofol, either by continuous infusion or as a bolus (1 mg/kg) just before the end of surgery, showed a protective effect against sevoflurane-induced ED. 14,15 An induction dose only had no effect. 8 Although ketamine has been used to reduce ED, ketamine itself can result in ED.…”
Section: Manipulation Of Volatile Agentsmentioning
confidence: 94%
“…The incidence of ED varies between 20% and 80% depending on the scoring system used [3,5,6]. Different drugs, including analgesics [7,8], benzodiazepines [9], a 2 -adrenergic receptor agonists [10] and propofol [11] have been used, with varying success.…”
Section: Introductionmentioning
confidence: 99%
“…Propofol is commonly used for conscious sedation and induction/maintenance of general anaesthesia. Several studies evaluating the effectiveness of these agents separately in reducing ED following sevoflurane anaesthesia have shown positive results [2,[11][12][13][14]. However, Bong et al recently reported that there was no significant decrease in the incidence of ED with either of these drugs in children receiving general anaesthesia with sevoflurane for magnetic resonance imaging (MRI) [15].…”
Section: Introductionmentioning
confidence: 99%